How does digital inclusive finance enhance rural economic resilience? — A study based on provincial panel data in China - Yunlong Ma; Ruolan Wei; Huina Bi (PLoS ONE, 2025)
This paper explores the role of digital inclusive finance in enhancing rural economic resilience, using panel data from 30 Chinese provinces, municipalities, and autonomous regions from 2013 to 2023. The results show that digital inclusive finance significantly improves rural economic adaptability and transformation capabilities, though its impact on risk resistance is minimal. It strengthens rural economic resilience through two main channels: improving transportation infrastructure and promoting rural technological innovation. This effect is particularly strong in areas with advanced rural digital infrastructure. Heterogeneity analysis reveals that digital inclusive finance positively impacts rural economic resilience in both eastern and western regions, but has no significant effect in central regions. Furthermore, its impact is more pronounced in non-agricultural provinces compared to agricultural ones. The study suggests that the government should continue expanding digital inclusive finance, while tailoring policies to local conditions, to support the sustainable development of the rural economy.